Penerapan Pengering Surya-Tungku Termodifikasi Dalam Peningkatan Produktivitas dan Higienitas Produksi Ikan Asin Tanpa Formalin Nelayan Pantai Congot, Kulonprogo, Daerah Istimewa Yogyakarta - Devi Yuni Susanti; Prihati Sih Nugraheni; Anang Hermawan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2015)
Salted fish is a fish product with simple preservation method as a solution to increase value added, extend shelf life and expand the distribution chain, and provide convenience and distinctive taste to be consumed. The groups of small industries and marketer “POKLAHSAR SRIKANDI” and “BOGOWONTO” have produced 10-50 kg salted fish per day. The fish is taken from Congot coastal areas, to increase its value added when it was in low price because it was abundant and to maintain the stability of Pohlaksar’s income when it was scarcity. Both the POKLAHSAR have commitment to produce healthy salted fish (without formaldehyde) but they had problem, especially in the rainy season, in drying process that took a long time and attrack the flies so it can be harmfull. Program of Science and Technology for community has applied dryer as innovation product to improve productivity, hygiene and quality of salted fish. The dryer which was made of affordable material, has affordable operation manner and maintenance, so it can be adopted by fishermen. The design of dryer combine solar heating systems and air heating units using modified furnaces. This dryer is capable to dry 25 kg of fresh fish by reducing their water content from 72.2% to 12.3% within 9 hours. The salted fish processed within this dryer was more white, crunchy and not fishy than the salted fish dried by convensional drying. In addition, the programs also consist of packaging advisory, marketing and business coach to trigger the motivation of both POKLAHSAR for their development and sustainability.